Total phenolic content, antioxidant and cytotoxic activity of cocoa (Theobroma cacao L.) polyphenols extracts on cancer cell lines - A. R., Hazirah; B., Zainal; Md. Akim, Abdah (Nutrition Society of Malaysia, 2013)
Introduction: Cancer chemopreventive agents from natural sources have been actively investigated over the years to seek prevention against cancer. In this study, cocoa polyphenols extract (CPE) was examined to explore its antioxidant and cytotoxicity activities.